JINGLE BELLS IN THE HISTORICAL WAYS OF CAROL SONGS - D. R., Fancy; Joseph, Solomon Asha; Mathew, Leena Liz; S., Saran (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Carols traditionally held a central place in the celebration of the Christmas season. It is believed that the angels sang the first carol on the day of Jesus’ birth on the first Christmas night. But Carols before the birth of Jesus come to our attention as we travel through history. The beginning of the carol is detailed in history as it was part of the Winter Solstice celebration. There was also a time when carols were written and sung for all four seasons. May carols, Harvest carols etc. were celebrated. Thus in the beginning, Christmas carols were more secular rather than sacred and religious. The secularization didn’t destroy the significance of this carols, it only took the celebration back to its roots and reminded us of the social significance of early secular carols. However, it is a fact that the tradition of singing carols at Christmas only continued later. Many carols today have little to do with Christmas. Are they good signs that carols are becoming secular like in the early days? In the world of music, many songs have been composed about Sacrifice, Love and Peace. How Christmas carols have lasted so long, remaining in people’s minds for centuries and millennia? A study in search of the roots of the Christmas Carols is intended here. An attempt has also been made to associate the immortal Christmas Carols to the centuries in which they were born.